The Use of Coping Cards in Depressive Patients with Suicidal Ideation - Propientong, Ploypailin; Tantrarungroj, Thanita; Prachason, Thanavadee (Journal of the Psychiatric Association of Thailand, 2021)
Objective: Coping card is one of strategies used to remind the safety plan for patients with suicidal ideation. It usually come in the form of index card that can be easily accessed in crisis situation. This study aimed to evaluate the use of coping card in patients with major depressive disorder in coping with suicidal ideation and also the users’ perspective. Method: Uncontrolled longitudinal study in 21 patients with major depressive disorder and suicidal ideation was conducted at a psychiatric outpatient department, Ramathibodi Hospital. Scale for Suicidal Ideation (SSI-Thai), Depressive Symptom Index-Suicidality (DSI-SS), Patient Health Questionnaire (PHQ-9) were assessed before the study and at 4 weeks after the intervention with coping cards. Participants were introduced to coping cards and instructed to fill in coping strategies previously discussed with their clinician in the safety planning process. Descriptive and analytical statistics using Wilcoxon signed rank test, paired sample T-test and Fisher’s Exact Test were used. Results: From baseline to the 4-week assessment, there was a reduction in the mean scores of SSI, DSI-SS and PHQ-9 with a difference of 2.40±5.83 points for SSI (p = 0.09, Cohen’s d = 0.454), 0.80± 3.11 points for DSI-SS (p = 0.02, Cohen’s d = 0.30) and 2.65±45.57 points for PHQ-9 (p<0.01, Cohen’s d = 0.63). None of the participants engaged in suicidal behaviors within the 4-week study period. Almost all of the participants kept their coping cards and remembered the coping methods in the card. A non-statistically significant difference in demographic data, SSI score and PHQ-9 score was found between coping card users and non-users. Participants found the coping card most useful for reminding them of the coping strategies including using distraction. Conclusion: Coping card is a simple, brief intervention that is potentially helpful for dealing with suicidal ideation by objectively reminding the coping strategies. Most participants remember coping methods and have used those methods. Key words: Coping card, suicidal ideation, major depressive disorder